1984
DOI: 10.1084/jem.159.2.604
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit and rat C-reactive proteins bind apolipoprotein B-containing lipoproteins.

Abstract: Immobilized rabbit and rat C-reactive protein (CRP) were found to selectively bind apolipoprotein B (apoB)-containing lipoproteins (low density lipoprotein, LDL and very low density lipoprotein, VLDL) from whole serum in a manner similar to that previously reported with human CRP. In acute phase human serum the CRP is in a free form, not complexed with lipoprotein or any other macromolecular ligand, and in acute phase serum from most rabbits fed on a normal diet the rabbit CRP was also free. However, in acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…The discrepancy between our study and a previous study is clearly due to the extreme differences in blood cholesterol levels of the subjects. It has been reported that CRP can selectively bind to apoB-containing atherogenic lipoproteins; such as VLDL and LDL, in hypercholesterolemic rabbits as well as in humans, 34 thus increased levels of LDL-C may facilitate the formation of CRP-lipoprotein complexes in circulation. Furthermore, hypercholesterolemia may induce systemic inflammatory response through overproduction of oxidized LDL.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between our study and a previous study is clearly due to the extreme differences in blood cholesterol levels of the subjects. It has been reported that CRP can selectively bind to apoB-containing atherogenic lipoproteins; such as VLDL and LDL, in hypercholesterolemic rabbits as well as in humans, 34 thus increased levels of LDL-C may facilitate the formation of CRP-lipoprotein complexes in circulation. Furthermore, hypercholesterolemia may induce systemic inflammatory response through overproduction of oxidized LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we also studied activation of complement by native CRP interacting with ligands in rat plasma. The CRP baseline level in rats is about 0·5 g/l 8,30–32 . Hence, we studied activation of complement via CRP by incubating NRP with different CRP ligands, without additional CRP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…23 CRP (60 g) was incubated with 0, 0.1, 1, or 10 g phosphorylcholine (obtained from Sigma) in HEPES/Ca 2ϩ buffer for 30 minutes. Thereafter, E-LDL (500 g cholesterol) was added to each sample, and incubation continued for another 30 minutes.…”
Section: Quantitative Assessment Of Crp-binding To Ldlmentioning
confidence: 99%